PRESERVATION OF STATUS QUO OR INTER-ETHNICITY RELATION THE DYNAMICS OF MALAY-CHINESE ECONOMIC RELATION IN THE NORTHERN COAST AREA OF WEST KALIMANTAN - Fachrurrazi, Fachrurrazi (I-Economics, 2019)
The ideal goal of interactions that an ethnic group performs within itself or with other ethnic groups entails more than mere actualization of values; good and bad, proper and improper, right and wrong. The diverse ethnic groups living together in the Northern Coast of West Kalimantan which covers: Bengkayang Regency coasts, Singkawang City, and Sambas Regency have revealed at least three dominant local ethnic groups, i.e. Dayak, Malay, and Chinese. The dynamics of economic relation between Malay and Chinese people in the Northern Coast of West Kalimantan, from Functional Structural perspective and regarding Malay economic actors in Sambas Regency and Chinese economic actors in Singkawang City both were based on ethnic dominance—was deliberately created as an effort to strengthen system stability or status quo for the interest of the dominant group. From non-functional perspective, the analysis began on the concept of society as a complex social system, in which economic competition was a sub-system; both were functionally interdependent. Society could become a means to realize a conflict of power because job and earnings were distributed unfairly and differently